Tophaceous gout of the nose in a male FMR1 premutation carrier. Issue 11 (27th November 2022) - Tang, Si Jie; Giri, Shanthi; Pahlavan, Nima; Han, Sophia H.; Santos, Ellery R.; Espinal, Glenda; Aishworiya, Ramkumar; Schneider, Andrea; Hessl, David; Rivera, Susan M.; Hagerman, Randi J.
Abstract: Premutation alleles with 55–200 CGG repeats in FMR1 can lead to fragile X‐associated tremor/ataxia syndrome (FXTAS). In this case study, we report uncontrolled gout in a 68‐year‐old male with FXTAS with multiple sites of involvement including a rare gouty tophus in the nasal region. Abstract : This is the first documentation of immune dysregulation manifesting as uncontrolled gout in a male FXTAS premutation carrier. There is a need for further investigation of immune‐mediated disorders in male FXTAS carriers.